Entrepreneurship Interest by Solely Micro, Small and Medium Enterprises During Covid-19 Outbreak - Asi, Yuli Sintha; Christiana, Ansita (Universitas Dr. Soetomo, 2021)
The purpose of this article is to discuss in more detail both internal and external factors causing entrepreneurship interest as a solely or a small group enterprise. The purpose is also to find out 1). The Interest of the students in Sekolah Tinggi Ilmu Ekonomi Sampit ( The Institute of Economic Sciences ) Sampit in becoming Enterpreneurs 2). What are the factors that causes the students’ interests in becoming Enterpreneurs ?. Methodology of this research is descriptive qualitative. The qualitative approach is used to examine interests in becoming Entrepreneurships as well as the factors.Data collection for this research is through study literatures, field observation, questionnaires and deep interviews. The finding of this research shows low interest of being entreprenurship as the effect of covid 19 outbreak. The external factors that cause low interest of being a solely entrepreneur is shown through the procentage , it is less than 18% . While average procentage of the internal factors is at 9%-18%. The original value of this article is that to increase interest of being solely micro, small and medium enterprises should be supported with the change of learning system in which 60% practices rathen than theory in this Covid-19 pandemic. The implementation of theory in the real situation as an enterpreneurs.